Method for Rapid Detection of Group B Streptococci by Coagglutination - Leland, Diane S. (1978)
A quick and reliable technique for the identification of group B streptococci has been developed. The method requires no elaborate equipment or expensive reagents and can be used to detect the group B organisms in mixed broth cultures or to identify suspect colonies selected from agar plates. The method is a coagglutination technique in which 1 drop of specifically sensitized protein A-containing Staphylococcus aureus is mixed with 1 drop of supernatant of an actively growing culture. The soluble group-specific carbohydrate substance of the group B streptococci reacts with the staph particles to produce agglutination that is macroscopically readable. One colony of group B streptococci taken from an agar plate and inoculated into Todd-Hewitt broth will give a positive reaction within 6 h of incubation; with a larger inoculum, the positive reaction occurs within a shorter period. The method was applied for detection of group B streptococci in mixed broth cultures. In laboratory studies involving random mixtures of organisms, 59.3% of positive cultures were detected within the first 8 h of incubation, and 71.7% were found within 24 h. In clinical studies with mixed broth cultures grown directly from vaginal swabs, 78.6% of the positive cultures were detected within the first 8 h of incubation, and 92.9% were found within 24 h.